Gerakan Literasi Dasar Upaya Pengentasan Buta Aksara di Kalangan Santri Dayah - Putriana; Rizayanti (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
The Basic Literacy Movement was successfully conducted at Dayah Darut Thalibin, Gampong Pasir Putih, Peureulak Subdistrict, East Aceh Regency, from January 10 to 15, 2025. This program involved 10 beginner-level santri who initially had inadequate reading and writing skills. Based on the pre-test results, 60% of participants were classified as functionally illiterate, 30% could recognize letters but were not fluent in reading or writing, and 10% could read simple sentences but struggled with writing. The training employed a participatory and contextual approach rooted in religious teachings, utilizing interactive and hands-on methods such as reading daily prayers, short Qur’anic verses, and copying hadiths. The activities were conducted over six days in morning and afternoon sessions, supported by peer tutors and guidance from ustadz. Post-test results showed that 80% of the santri successfully achieved basic reading and writing skills, 10% showed limited progress, and 10% had no significant improvement. Overall, the program improved the santri’s literacy skills by 70%. Beyond technical skill development, the program fostered enthusiasm for learning and increased self-confidence among the santri, motivating the dayah to continue and expand the literacy program sustainably. This initiative demonstrates that literacy education is most effective when tailored to the participants’ context and needs.